Petrographic examination of ledge rocks aided by microscopic and X-ray diffraction analyses for alkali-silica reactivity - Tamrakar, Naresh Kazi; Paudel, Lalu Prasad (Bulletin of the Department of Geology, 2011)
Presence or absence of deleterious constituents and alkali-silica reactivity are especially important when aggregates are to beused in concrete structures. A ledge rock sample was petrographically analysed for alkali-silica reactivity. In overall, two rockclans (metasiltstone and metasandstone) with nine sub clans were identified from the ledge rock sample. All the rock types werewell interlocked, indurated, and cemented extensively by calcite. All the silica grains were low quartz. Except a trace amount ofchert containing microquartz in rock type C, reactive silica such as amorphous silica and high-quartz are absent. Instead, illite inmany rocks and vermiculite in rock types C and D were deleterious silicate components, which in the whole rock sample were5% and 2%, respectively. Presence of vermiculite and illite is found to be strongly controlled by the presence or absence of clayeypartings in metasiltstones and metasandstones.DOI: http://dx.doi.org/10.3126/bdg.v14i0.5435Bulletin of the Department of Geology Vol.14 2011, pp. 21-28